International human rights and indigenous peoples - Anaya, S. James (New York, NY : Aspen Publishers, 2009)
"This exciting new book is the only one of its kind. International Human Rights and Indigenous Peoples (Aspen Elective Series) will be the first published compilation of materials and commentary intended for use in courses focusing on the subject of indigenous peoples within the international human rights system. S. James Anaya, co-author of the well-known casebook, International Human Rights: Problems of Law, Policy and Practice, uses carefully edited material from varied sources to illustrate the major issues facing indigenous peoples today."--Pub. desc.
Indigenous peoples and the international system -- The United Nations Declaration on the Rights of Indigenous Peoples : its content, status, and practical meaning -- International Labour Organization Convention No. 169 on indigenous and tribal peoples -- United Nations treaty regimes and their application to indigenous issues -- The inter-American system for the protection of human rights as applied to indigenous peoples.
Includes bibliographical references and index.
Keywords: Human rights; Indigenous peoples -- Legal status, laws, etc; Indigenous peoples (International law); Human rights; Indigenous peoples (International law); Indigenous peoples -- Legal status, laws, etc